A METHOD FOR ESTIMATING THE DISPLACEMENT OF OBJECTS BY ANALYZING IMAGES WITH A CIRCULAR COLOR GRADIENT IN THE PROBLEM OF MEASUREMENT IN TECHNICAL SYSTEMS - VUSATYI , NIKITA; PASICHNYK, OLEKSANDR; MANZIUK, EDUARD; SKRYPNYK, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The current stage of human development can be characterized as an incredibly large amount of information in the digital industry. Observing this, we can safely say that the digital industry has completely replaced and automated life and activities. As noted above, today there is a growing trend towards the full penetration of intelligent information technologies into all spheres of human activity, often accompanied by the use of various digital technical devices. One of the recent stable trends is the widespread use of imaging devices even in everyday life. At the same time, there is a growing need to determine the presence or absence of displacement of objects of observation. These circumstances create opportunities for solving this problem by comparing successive images, which allows not only to qualitatively assess the presence of displacement, but also to measure its magnitude. This approach makes it possible to solve measurement problems in technical systems. The key issue that determines the potential accuracy in a measurement task is the most accurate measurement of the position of the object of observation against the background of others. In general, the observer deals with a gradient change in color under both natural and artificial lighting conditions, and the task of determining the position of the object of observation is actually to analyze images with a circular color gradient.